Bruce Bronzan for State Assembly Fundraiser at Saroyan Theatre with Willie Brown - Watkins, Howard::::::::: (1984)
Bruce Bronzan welcoming Speaker of the California State Assembly Willie Brown to stage Bronzan for State Assembly poster on wall